Mortality-related factors in patients with OXA-48 carbapenemase-producing Klebsiella pneumoniae bacteremia. Issue 14 (9th April 2021) - Rodríguez, O. Lima; Sousa, A.; Pérez-Rodríguez, María Teresa; Martínez-Lamas, L.; Suárez, R. Longueira; Martínez, C. Taboada; Pino, C. Portela; Vidal, F. Vasallo; Pérez-Landeiro, A.; Casal, M. Crespo
Abstract : Abstract: Carbapenemase-producing Enterobacterales constitute a serious public health threat; however, information on the oxacilinasa (OXA-48)-type is limited. The objective of the study was to evaluate the risk factors associated with 14-day mortality for patients with bacteremia due to OXA-48 carbapenemase-producing Klebsiella pneumoniae . We conducted a retrospective, single-center observational study of adult patients with K. pneumoniae bacteremia, classifying the strains as carbapenem-susceptible K. pneumoniae (CSKp) and carbapenem-resistant K. pneumoniae (CRKp). All of the CRKp strains were the OXA-48-type. The study included 202 cases of bacteremia: 114 due to CSKp and 88 due to CRKp. The clinical cure rate was higher for the patients with CSKp (85% vs 69% for CSKp and CRKp, respectively; P = .010), while the 14-day mortality rate was lower (13% vs 30%, P = .005). An INCREMENT-CPE score ≥7 (HR 3.05, 95% CI 1.50–6.25, P = .002) was the only independent factor associated with 14-day mortality for the patients with Klebsiella spp. bacteremia. Other factors related to 14-day mortality were a rapidly fatal prognosis (McCabe) (HR 7.1, 95% CI 2.75–18.37, P < .001), dementia (HR 5.9, 95% CI 2.0–7.43, P = .001), and a high-risk source of infection (HR 2.7, 95% CI 1.06–6.82, P = .038). The most important factors associated with 14-day mortality for the patients with K. pneumoniae bacteremia was an INCREMENT-CPE score ≥7, dementia, a McCabe score indicating a rapidly fatal prognosis and a high-risk source of infection. We found no relationship between a poorer outcome and CRKp isolation or inadequate antibiotic therapy.